Golbal Malay Writing - The Sun, (2008)
Lim Swee Tin is one of only a few non-Malays who wax lyrical in Malay, evemn writing books in the language of Chinese-Thai parentage. He has been writing for 37 years and has won more than 20 awards, including the sea write award fron Thailand and the Perdana Literary Award. The prolific wariter has produced 18 books of poems have been transled into English, Russian and Korean. Lim, 55, has been invited to recite his poems in Thailand, Taiwan dan Britian. A literature lecturer at Universiti Putra Malaysia. He also sit on the National Language Ministrie. Lim laments to Bissme S. about the dearth of good literary works in Malay and how Malaysians do not read. Nevertheless, he dreams of seeing a Malaysian win the novel proze for literature.